The Influence of Self Mastery Agenda, Change Diagnosis Agenda, Innovation Agenda and Effective Team Agenda on Adaptive Leadership Relating to Regional Development (Case Study on Echelon III Officials in North Sumatra Province) - Syahrizal; Tarmizi, H.B.; Rujiman (Journal of Environmental and Development Studies, 2021)
Regional development is one of the efforts in order to utilize the potential of the existing area to obtain better conditions and life arrangements for the benefit of the community. For this reason, in the effort to develop regional areas, the government hopes that through the implementation of training and education, change leaders will be able to make changes and adapt to changes that occur in their environment. These changes were made in order to maintain the organization with a high level of performance. There are several agendas that become factors in influencing the formation of adaptive leadership in the implementation of education and training teams, namely the self mastery agenda, the diagnostic reading agenda, the innovation agenda and the effective team agenda. The purpose of this research is to determine the effect of the self mastery agenda, diagnostic reading agenda, innovation agenda, and effective team agenda on adaptive leadership and its relation to regional development. The method of analysis used in this research is multiple linear regression using descriptive methods through a quantitative approach. The number of respondents is 160 people. The results showed that: the self mastery agenda had a positive and significant effect on adaptive leadership, the diagnostic reading agenda had a positive and significant effect on adaptive leadership, the innovation agenda had a positive and significant effect on adaptive leadership, the effective team agenda had a positive and significant effect on adaptive leadership and there were a fairly close relationship between adaptive leadership to regional development.